Le campagne lombarde, tessera chiave del mosaico agrario europeo - Antonio Saltini (Glocalism: Journal of Culture, Politics and Innovation, 2014)
A comprehensive historiography of the agricultural development in continental Europe, from the medieval period until the XX century, does not exist. Indisputably, modern agriculture is essentially an outgrowth of the humid temperate regions bordering the English Channel, but English, French and German scholars were wrong to identify these regions as the only cradle of the modern agricultural revolution.